Full-endoscopic uniportal retropharyngeal odontoidectomy for anterior craniocervical infection. Issue 3 (4th May 2019) - Ruetten, Sebastian; Hahn, Patrick; Oezdemir, Semih; Baraliakos, Xenophon; Godolias, Georgios; Komp, Martin
Abstract: Background: Infections of the anterior craniocervical junction may require surgery. There are various techniques with individual advantages and disadvantages. This study evaluates the full-endoscopic uniportal technique via the anterior retropharyngeal approach for odontoidectomy, decompression, and debridement. Material and methods: Three patients with an infection of the anterior craniocervical junction with retrodental involvement were operated on between 2014 and 2016 using the full-endoscopic uniportal technique. Posterior stabilization was also performed with the same procedure for all patients. Results: The operation was technically satisfactory in all cases. No problems due to swelling of the pharyngeal soft tissue occurred. No other complications were observed. All patients had a satisfactory outcome with stable regression of the myelopathy symptoms and/or complete healing of the infection. The follow-up images showed sufficient decompression of bone and soft tissues in all cases. Conclusions: The full-endoscopic uniportal technique with an anterior retropharyngeal approach can be an adequate and minimally invasive surgical technique for odontoidectomy, decompression, and debridement in infections of the craniocervical junction and can reduce access-related problems. The transoral, transnasal, and retropharyngeal approaches have different surgical fields due to the access trajectories, which must be taken into consideration depending on the anatomy and pathology when selecting a suitable technique.